Knowledge of Gout Disease among Saudi Adult Population in Riyadh City, Saudi Arabia - Kaabba, Abdulaziz Fahad Al; Altamimi, Noora Omar; Alqumayzi, Muzun Mohammed; Alshahrani, Khawlah; Aldalbahi, Atheer; Al-Rajeh, Htoun; Alkanaan, Dalal (Disease and Health Research: New Insights Vol. 11, 2024)
Gout is a painful chronic inflammatory disease that causes swelling, redness, and tenderness in the joints. Gout results from elevated uric acid levels in the blood, leading to the formation of sharp urate crystals in the joints, often causing sudden, severe pain and inflammation, especially in the big toe. Despite the fact that it is a serious condition, the level of attention is extremely low. Gout is the most common type of inflammatory arthritis, and it can have a negative impact on one's quality of life. The purpose of this study is to assess gout disease knowledge among male and female adults in Riyadh, Saudi Arabia, in 2020. The method of this study was a cross-sectional study, 500 participants were randomly selected (50% were males, 50% were females), and data were collected using a pre-tested electronic questionnaire. The result of the study's findings indicated that adults in Riyadh city were knowledgeable about gout disease, with 73.2% of participants having a good level of knowledge. 10.4% of the participants had previously been diagnosed with gout disease, and they frequently rely on starches and legumes (17.6%), chickens (16.4%), and vegetables and fruits (12.8%) for their diet. Our findings show that as one gets older and more educated, one's level of awareness rises. Adults in Riyadh, Saudi Arabia, were sufficiently aware of the gout disease. The majority of the participants appeared to be aware of the symptoms and causes of gout disease. There was a significant relationship between age, marital status, level of education, occupation, and participants with gout disease. Participants who had been diagnosed with gout disease often depended on carbohydrates and legumes, chickens, vegetables and fruits for their diet.